High-magnesian calcite mesocrystals: A coordination chemistry approach - Lenders, Jos J. M.; Dey, Archan; Bomans, Paul H. H.; Spielmann, Jan; Hendrix, Marco M. R. M.; De With, Gijsbertus; Meldrum, Fiona C.; Harder, Sjoerd; Sommerdijk, Nico A. J. M. (Journal of the American Chemical Society, 2012)
While biogenic calcites frequently contain appreciable levels of magnesium, the pathways leading to such high concentrations remain unclear. The production of high-magnesian calcites in vitro is highly challenging, because Mg-free aragonite, rather than calcite, is the favored product in the presence of strongly hydrated Mg ions. While nature may overcome this problem by forming a Mg-rich amorphous precursor, which directly transforms to calcite without dissolution, high Mg /Ca ratios are required synthetically to precipitate high-magnesian calcite from solution. Indeed, it is difficult to synthesize amorphous calcium carbonate (ACC) containing high levels of Mg, and the Mg is typically not preserved in the calcite product as the transformation occurs via a dissolution-reprecipitation route. We here present a novel synthetic method, which employs a strategy based on biogenic systems, to generate high-magnesian calcite. Mg-containing ACC is produced in a nonaqueous environment by reacting a mixture of Ca and Mg coordination complexes with CO . Control over the Mg incorporation is simply obtained by the ratio of the starting materials. Subsequent crystallization at reduced water activities in an organic solvent/water mixture precludes dissolution and reprecipitation and yields high-magnesian calcite mesocrystals with Mg contents as high as 53 mol %. This is in direct contrast with the polycrystalline materials generally observed when magnesian calcite is formed synthetically. Our findings give insight into the possible mechanisms of formation of biogenic high-magnesian calcites and indicate that precise control over the water activity may be a key element. © 2011 American Chemical Society.